TOE drivers for cloud transformation: direct or trust-mediated?. Issue 2 (13th April 2015) - LI, Min; Zhao, Dingtao; Yu, Yan
Abstract : Purpose: – The purpose of this paper is to explain cloud service transformation in small and medium enterprises (SMEs) based on technology-environment-organization paradigm and understand the role of cloud service trust in transformation process. Design/methodology/approach: – A survey involving 107 SMEs was conducted to examine the research model and hypotheses. Findings: – First, cloud service trust is found to have a significant positive effect on the SMEs' cloud service transformation intention. The second finding is about significant influences of technological drivers (reliability and information security), environmental drivers (institutional pressure, structure assurance, and vendor scarcity) and entrepreneurship on SMEs' cloud service trust. Further, the authors found mediating effects of trust on relationships between external drivers and cloud service transformation. Practical implications: – For vendors, it suggests building cloud service trust by distinguishing advantages of their cloud service and by establishing strategic alliances with existing users in marketing to attract potential clients. Vendors should target entrepreneurial organizations as initial customers and then expand to other types of organizations. For users, the study implies the need of cultivating entrepreneurship, if they have innovative IT initiatives and need to speed up the IT innovation absorption. Market regulators can provide adequate structural assurances and survival-of-the-fittest market mechanism to stimulate cloud service market. Originality/value: – This study is on the leading edge of systematically investigating drivers for SMEs' cloud service transformation and further reveals a mediating process, in which technological and environmental aspects have primary effects on cloud service trust that sequentially influences cloud service transformation. These mediating effects imply an essential trust building process of cloud service transformation.